Stereotactic radiosurgery for melanoma brain metastases: Concurrent immune checkpoint inhibitor therapy associated with superior clinicoradiological response outcomes. Issue 4 (27th March 2022) - Shanker, Mihir D; Garimall, Sidyarth; Gatt, Nick; Foley, Heath; Crowley, Samuel; Le Cornu, Emma; Muscat, Kendall; Soon, Wei; Atkinson, Victoria; Xu, Wen; Watkins, Trevor; Huo, Michael; et al.
Abstract: Introduction/purpose: This study assessed long‐term clinical and radiological outcomes following treatment with combination stereotactic radiosurgery (SRS) and immunotherapy (IT) for melanoma brain metastases (BM). Methods: A retrospective review was performed in a contemporary cohort of patients with melanoma BM at a single tertiary institution receiving Gamma Knife ® SRS for melanoma BM. Multivariate Cox proportional‐hazards modelling was performed with a P <0.05 for significance. Results: 101 patients (435 melanoma BM) were treated with SRS between January‐2015 and June‐2019. 68.3% of patients received IT within 4 weeks of SRS (concurrent) and 31.7% received SRS alone or non‐concurrently with IT. Overall, BM local control rate was 87.1% after SRS. Median progression free survival was 8.7 months. Median follow‐up was 29.2 months. On multivariate analysis (MVA), patients receiving concurrent SRS‐IT maintained a higher chance of achieving a complete (CR) or partial response (PR) [HR 2.6 (95% CI: 1.2–5.5, P = 0.012)] and a reduced likelihood of progression of disease (PD) [HR 0.52 (95% CI: 0.16–0.60), P = 0.048]. Any increase in BM volume on the initial MRI 3 months after SRS predicted a lower likelihood of achieving long‐term CR or PR on MVA accounting for concurrent IT, BRAF status and dexamethasone use [HR = 0.048 (95% CI: 0.007–0.345, P = 0.0026)]. Stratified volumetric change demonstrated a sequential relationship with outcomes on Kaplan–Meier analysis. Conclusion: Concurrent SRS‐IT has favourable clinical and radiological outcomes with respect to CR, PR and a reduced likelihood of PD. Changes in BM volume on the initial MRI 3 months after SRS were predictive of long‐term outcomes for treatment response.